Joint scheduling and resource allocation for device-to-device underlay communication - Feiran Wang; Lingyang Song; Zhu Han; Qun Zhao; Xiaoli Wang (2013 IEEE Wireless Communications and Networking Conference (WCNC), 2013)
Device-to-device (D2D) communication as an underlay to cellular networks can bring significant benefits to users' throughput. However, as D2D user equipments (TIEs) can cause interference to cellular TIEs, the scheduling and allocation of channel resources and power to D2D communication need elaborate coordination. In this paper, we propose a joint scheduling and resource allocation scheme to improve the performance of D2D communication. We take network throughput and TIEs' fairness into account by performing interference management. Specifically, we develop a Stackelberg game framework in which we group a cellular TIE and a D2D TIE to form a leader-follower pair. The cellular user is the leader, and the D2D TIE is the follower who buys channel resources from the leader. We analyze the equilibrium of the game, and propose an algorithm for joint scheduling and resource allocation. Finally, we perform computer simulations to study the performance of the proposed algorithm.